The effects of proactive approach and integrated medical care on psychological distress in hospitalized patients: A single center experience. Issue 4 (11th August 2022) - Wu, Chiu‐Feng; Lin, Ting‐Yun; Liu, Yi‐Ting; Tzeng, I‐Shiang; Wu, Fang‐Chien; Lin, Chia‐Te; Chao, You‐Chen
Abstract: Purpose: Psychological distress is common among patients with acute diseases and is associated with a poorer prognosis. Early detection and intervention are important for high‐risk individuals. Design and Methods: This retrospective study used the five‐item Brief Symptom Rating Scale (BSRS‐5) to assess psychological distress and evaluate whether proactive intervention may reduce distress levels among hospitalized patients in a single medical center in northern Taiwan. Findings: Of the patients, 10.7% were found to have varying degrees of emotional distress (BSRS‐5 ≥ 6). After providing integrated medical care for patients with psychological distress, the degree of stress decreased significantly ( p  < 0.001). These results were consistent across subgroups. Practice Implications: The results highlight that proactive assessment and appropriate interventions may reduce patients' psychological distress during their course of hospitalization.